Tinjauan Yuridis Pertanggungjawaban Pencemaran Minyak di Wilayah Teluk Balikpapan - Elisabeth Septin Puspoayu; Arief Rachman Hakim; Hanum Selsiana Bella (Jurnal Hukum IUS QUIA IUSTUM, 2018)
Environmental  pollution  in  Balikpapan  Bay  due  to  the  leaking  of  Pertamina  oil  pipeline  is  a  serious problem because it pollutes the marine ecosystem, resulting in disruption of environmental functions. However, the pollution caused by the burst pipeline due to the anchor of the MV Judger vessel cannot be directly imposed by the accountability mechanism as stipulated in Law on Environmental Protection and Management because there is no single factor in the incident. This paper aims to construct the form of accountability that must be done when an environmental pollution cannot be found as a single factorof error and involves the subject of international law outside the jurisdiction of the country where the pollution  occurs.  The  type  of  research  used  is  normative  juridical.  The  result  shows  that  joint accountability in the perspective of civil law is the best solution because the absence of a single factor and the existence of force majeure require that the parties involved in the shipping also be responsible for the pollution.